The Role of Human Resource Flexibility and Organization Ambidexterity in Increasing Organizational Performance - Laksmi Sito Dwi Irvianti; Agus Rahayu; Lili Adi Wibowo; Alfira Sofia (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
In order to have good quality human resources, then we need to provide better education for the society. For this reason, universities must have an excellence performance to create a high quality human resource. This study aims to find out the effect of Human Resource Flexibility and Organizational Ambidexterity toward Organizational Performance, partially and simutaneously. The population of this study is all universities in LLDIKTI III area that is located in Jakarta. Sampling techniques used is purposive sampling in which the respondent is the person who is fit with the criteria set before. Thus, the sample is 42 respondents who is a decision maker in universities with ‘Unggul ’accreditation. The data is collected by distributing questionnaire and then analyzed by using SEM-PLS. The result showed that Human Resource Flexibility and Organizational Ambidexterity have a significant effect toward Organizationa Performance partially. Beside, Human Resource Flexibility and Organization Ambidexterity have the effect toward Organizatioan Performance simutaneously.